2011
DOI: 10.1097/hjh.0b013e328340d76f
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and hypertension: a systematic review and meta-analysis of observational studies

Abstract: Quality of life of individuals with hypertension is slightly worse than that of normotensive individuals. The influence of high blood pressure and of the awareness to have hypertension requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
184
0
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 34 publications
14
184
0
21
Order By: Relevance
“…We also found a negative association between high blood pressure and HRQoL. Such an association has previously been found in the general population with hypertension, although the difference compared with normotensive individuals is rather small (Trevisol et al, 2011). From a clinical perspective, treatment of hypertension seems important as good blood pressure control can improve HRQoL (Zygmuntowicz et al, 2013).…”
Section: Comparisons With Other Studiessupporting
confidence: 77%
“…We also found a negative association between high blood pressure and HRQoL. Such an association has previously been found in the general population with hypertension, although the difference compared with normotensive individuals is rather small (Trevisol et al, 2011). From a clinical perspective, treatment of hypertension seems important as good blood pressure control can improve HRQoL (Zygmuntowicz et al, 2013).…”
Section: Comparisons With Other Studiessupporting
confidence: 77%
“…11,12 A systematic review of 20 original contributions identified lower quality of life among hypertensive individuals in most but not all studies. 13 Studies that could be included in a meta-analysis, and that had HRQoL evaluated by The Short-Form Health Survey (SF)-36 À or its reduced version SF-12 À , identified lower scores among individuals with hypertension or that reported to be hypertensive. 13 The studies were very heterogeneous with regard to selection criteria and comparison groups, limiting their external validity.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies that could be included in a meta-analysis, and that had HRQoL evaluated by The Short-Form Health Survey (SF)-36 À or its reduced version SF-12 À , identified lower scores among individuals with hypertension or that reported to be hypertensive. 13 The studies were very heterogeneous with regard to selection criteria and comparison groups, limiting their external validity. Moreover, some aspects on the relationship between high blood pressure (BP) and quality of life are still unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…[2] It is noted that the management and control of hypertension reduce morbidity and mortality, the percentage fluctuates between 5.4 and 58 % of patients with controlled hypertension, worldwide. [3] The uncontrolled hypertension may be related to worsened quality of life. [4] The relationships between patient, disease, treatment variables and HRQoL have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Lower HRQoL in patients with hypertension compared with normotensive individuals has been reported recent systematic review and meta-analysis of observational studies of health-related quality of life (HRQoL) in hypertensive patients. [3] This conceptual model suggests that physiological changes due to illness or treatment can lead to symptoms which affect functional status or HRQoL. These relationships are influenced by disease-related patient characteristics and environmental variables that may affect patient perception of symptoms and changes in HRQoL.…”
Section: Introductionmentioning
confidence: 99%